Regulation of protein tyrosine phosphorylation in boar sperm through a cAMP-dependent pathway - Kalab, P; Peknicová, J; Geussová, G; Moos, J (Molecular reproduction and development, 1998)
Changes of protein tyrosine phosphorylation in ejaculated boar sperm incubated in vitro were examined with the use of antiphosphotyrosine antibodies and immunoblotting. The intracellular levels of cAMP were modulated by treatment with various combinations of caffeine, 3-isobutyl-1-methylxanthine (IBMX), and dibutyryl cyclic AMP (dbcAMP), and acrosome reactions (ARs) were induced via treatment with divalent cation ionophore A23187. Proteins of Mr 34, 38, 40, and 44 (p34 ... p44) were strongly phosphorylated on tyrosine residues in freshly prepared sperm samples and at the same level during all subsequent treatments. Incubation of sperm in vitro for various periods of time induced an increase of tyrosine phosphorylation of p20, p93, and p175. The tyrosine phosphorylation of p93, p175, and several other sperm proteins was up-regulated in a concentration-dependent manner following treatment of the sperm with dbcAMP, caffeine, or IBMX alone, or with combinations of caffeine and IBMX, respectively, with dbcAMP; the tyrosine phosphorylation of p20 was not correlated with treatment of sperm with cAMP-elevating reagents. The percentage of sperm cells undergoing spontaneous ARs was not affected by the manipulation of cAMP levels and was not correlated with protein tyrosine phosphorylation. In contrast, the addition of calcium to the incubation media decreased protein tyrosine phosphorylation and elevated percentage of spontaneous ARs. The induction of ARs with A23187 caused a significant decrease of tyrosine phosphorylation of p93, p175, and p220/230, indicating that dephosphorylation on protein tyrosine residues might be associated with calcium influx during physiological ARs as well. Proteins p93 and p175 were effectively solubilized in greater than 9M urea/1% triton and in SDS sample buffer, but to only a small extent in triton, while p20 was virtually completely extractable with triton. In conjunction with the previously reported isolation of active tyrosine kinase sp42 from triton extracts of noncapacitated boar sperm cells (Berruti and Porzio, 1992: Biochim Biophys Acta 1118: 149-154), our results suggest that a cAMP-dependent event is required for tyrosine phosphorylation of triton-insoluble proteins such as p93 and p175. On the other hand, the tyrosine phosphorylation of p20 (and potentially other triton-soluble substrates) might not strictly require such cAMP up-regulation. We discuss the differences in the regulation of cAMP-dependent tyrosine phosphorylation in mouse, human, and boar sperm, and suggest that sensitivity to calcium and distinct basal levels of cyclic nucleotide PDE might correspond to species-specific reproduction strategies in mammals.
Keywords: signální transdukce; Phosphorylation; Signal Transduction; AMP cyklický; spermie; Humans; Tyrosine; fosforylace; lidé; zvířata; Cells, Cultured; myši; Cyclic AMP; Culture Media; Mice; Swine; kultivační média; Male; kultivované buňky; Spermatozoa; Animals; mužské pohlaví; tyrosin; prasata